Assessment of an active industrial exoskeleton to aid dynamic lifting and lowering manual handling tasks. (April 2018) - Huysamen, Kirsten; de Looze, Michiel; Bosch, Tim; Ortiz, Jesus; Toxiri, Stefano; O'Sullivan, Leonard W.
Abstract: The aim of this study was to evaluate the effect of an industrial exoskeleton on muscle activity, perceived musculoskeletal effort, measured and perceived contact pressure at the trunk, thighs and shoulders, and subjective usability for simple sagittal plane lifting and lowering conditions. Twelve male participants lifted and lowered a box of 7.5 kg and 15 kg, respectively, from mid-shin height to waist height, five times, both with and without the exoskeleton. The device significantly reduced muscle activity of the Erector Spinae (12%-15%) and Biceps Femoris (5%). Ratings of perceived musculoskeletal effort in the trunk region were significantly less with the device (9.5%-11.4%). The measured contact pressure was highest on the trunk (91.7 kPa-93.8 kPa) and least on shoulders (47.6 kPa-51.7 kPa), whereas pressure was perceived highest on the thighs (35-44% of Max LPP). Six of the users rated the device usability as acceptable. The exoskeleton reduced musculoskeletal loading on the lower back and assisted with hip extensor torque during lifting and lowering. Contact pressures fell below the Pain Pressure Threshold. Perceived pressure was not exceptionally high, but sufficiently high to cause discomfort if used for long durations. Highlights: The study assessed a trunk industrial exoskeleton for lifting and lowering. The exoskeleton reduced Erector Spinae and Biceps Femoris activity. Rating of musculoskeletal effort were lower with the exoskeleton. Measured and perceived pressure at the contacts was assessed. Exoskeletons can reduce body loadings, but the designs must be user centered.